Rupiah Exchange Rate Stability in the Shadow of Global Geopolitical Tensions: An Analysis of the Role of Bank Indonesia - Mustofa, Adhi (Economics Monetary Journal, 2025)
The increasing global geopolitical tensions of the last decade have triggered instability in international financial markets, with a notable impact on the exchange rates of emerging currencies, such as the Indonesian rupiah. The rupiah exchange rate, as a key indicator of macroeconomic stability, shows a sensitive response to the escalation of international conflicts such as the Russia-Ukraine war and tensions in the Middle East. This study aims to analyze the impact of geopolitical tensions on the rupiah exchange rate and evaluate the effectiveness of Bank Indonesia's responsive policies in maintaining monetary stability. Using a mixed-methods approach, this study combines quantitative analysis through the Autoregressive Distributed Lag (ARDL) and GARCH (1,1) models, as well as qualitative analysis through the examination of policy documents and market perceptions. The results of the study indicate that the Global Geopolitical Risk Index has a significant impact on the depreciation of the rupiah in both the short and long term. In addition, exchange rate volatility increased substantially during the period of geopolitical escalation, with Bank Indonesia's monetary policy response being effective in shaping market expectations through a forward guidance strategy and consistent policy communication. These findings underscore the importance of strengthening the credibility of monetary institutions and diversifying policy instruments in response to systemic external pressures. This study makes an empirical contribution to the understanding of exchange rate dynamics in the context of global uncertainty and the strategic role of central banks in maintaining national economic stability.